PENGARUH CARA EKSTRAKSI DAN KONSENTRASI PESTISIDA DARI DAUN TEMBAKAU TERHADAP PENEKANAN SERANGAN HAMA APHIS (Aphis croccivera Koch) DAN HASIL TANAMAN KACANG PANJANG (Vizna Sinensis L) - ENDANG SUPRAPTI; D. DARYANTI (JURNAL ILMIAH AGRINECA, 2008)
The Effect of extraction methode and concentration Of tobacco leaf extract for the Aphis pest (Aphis craccivora Koch) on yard long bean (Vigna Sinensis). This research was carried out at Bergas Kidul village, Bergas District, Semarang Regency with altitude 450 500 meter above the sea level. The aim of this research is to know the effect of extraction methode and concentration of tobacco leaf extract for the Aphis pest (Aphis craccivora Koch) on yard long bean (Vigna sinensis L). The research used the factorial experiment (2 x 5) with randomized completly design (RCD) in three replication. First factor; extraction methode of tobacco leaf: be boiled and be blended. Second la ctor; concentration : 0, 10, 20, 30, 40 ml / litre solution. The result of research showed that extraction methode of tobacco leaf non significant on the numbers of aphis pest, allact intensity of aphis, fresh weight of crown, dry weight of crown, numbers of pod yard long bean, weight of pod yard long bean, numbers of young pod yard long bean, weight of young pod yard long bean. Also that combination extraction-methode of tobacco leaf and concentration non significant on all parameter. Even though concentration of tobacco leaf extract significant for all parameters. The concentration of 10-30 ml / litre can control the aphis pest at yard long bean.